The Sensory And Protein Test On Dimsum Processes Shrimp (Penaeus merguensis) - Bashita Rizka Rachma; Youstiana Dwi Rusita; Suroso Suroso (Poltekkes Kemenkes Surakarta, 2021)
Background: Dimsum is a food from the Chinese region which is quite popular in Indonesia which has high nutritional value. Shrimp shells is one of the highest sources of active compounds for the amino acid group. This study was to determine the difference in protein content in dimsum cooked with different processing techniques. Methods: This type of research is descriptive with quantitative descriptive research design.The method used in this research is sensory test and quantitative analysis using a uv-vis spectrophotometer instrument. Ultraviolet light absorption measurements were carried out at a wavelength of 542 nm. This research were analyzed using univariate analysis which aims to explain and describe the characteristics of each research variable. And protein test result were made by plotting the absorbance value obtained against the concentration using the Microsoft excel. Results: The results showed that the shrimp dimsum had a protein content in GDK, KDK, GTK and KTK respectively 0,0307%; 0,0358%; 0,0385%; and 0,0521%. The statement that processing provides a decrease in protein levels, this is due to the use of high temperatures during the processing process resulting in denatured protein. The decrease in protein content is caused by the occurrence of denaturation and protein coagulation. The higher the temperature, the greater the amount of a densaturated protein, where at 50oC protein has experienced denaturation Conclusion: It is necessary to test the food quality of the processed shrimp dimsum (Penaeus merguensis) and further research needs to be developed using other better methods such as the Bradford method.